Phase diagram of a generalized Penson–Kolb–Hubbard chain with the occupation-dependent hopping - Jing Yu; Hanqin Ding (Results in Physics, 2023)
At half filling, we study analytically a one-dimensional correlated electronic system modeled by an extended Penson–Kolb–Hubbard (PKH) chain with the occupation-dependent hopping. The modification of the electron hopping amplitude is exhibited to induce the additional correlated-hopping interactions. At weak coupling, we use the field theory to obtain ground-state phase diagram, including the SDW, BCDW, BSDW, SS and TS phases for U>0. The induced three-body attractive interaction accounts for the superconductivity absent in the usual PKH model.